A Multi-Criteria Decision Support System for Burial Plot Selection Using the TOPSIS Method: A Web-Based Approach - Khoirunnisya Khoirunnisya; Muhamad Arief Yulianto (International Journal Software Engineering and Computer Science (IJSECS), 2026)
Rapid and accurate decision-making is essential in burial plot selection, particularly in urgent situations where families must simultaneously evaluate multiple criteria — price, available facilities, and land type. At TPU Al-Qobri, the absence of structured decision tools has allowed the manual selection process to persist, producing inconsistent outcomes and placing unnecessary burden on families during emotionally difficult circumstances. This study develops a web-based Decision Support System (DSS) using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to support objective burial plot selection based on multiple weighted criteria. System development follows the Software Development Life Cycle (SDLC), covering planning, analysis, design, implementation, testing, and maintenance phases. TOPSIS is applied to rank available burial plot alternatives and generate recommendations that are traceable and consistent across evaluation sessions. Testing results confirm that the system produces accurate rankings, reduces selection time, and improves administrative service management at the cemetery level. The proposed system demonstrates that structured, criterion-based decision support can replace subjective manual processes in public cemetery administration.